Queen Bees: How Is Female Managers’ Happiness Determined? - Xiong, Ailun; Xia, Senmao; Wang, Qing; Lockyer, Joan; Cao, Dongmei; Westlund, Hans; Li, Hongyi (Frontiers in Psychology, 2022)
This paper aims to study the determinants of subjective happiness among working females with a focus on female managers. Drawn on a large social survey data set (N=10470) in China, this paper constructs gender development index at sub-national levels to study how institutional settings are related to female managers’ happiness. We find that female managers report higher levels of happiness than non-managerial employees. However, the promoting effect is contingent on individual characteristics and social-economic settings. The full sample regression suggests that female managers behaving in a masculine way generally report a high level of happiness. Meanwhile, female managers who refuse to support gender equality report low happiness levels. Sub-sample analysis reveals that these causalities are conditioned on regional culture. Masculine behavior and gender role orientation significantly predict subjective happiness only in gender-egalitarian regions. This study is one of the first to consider both internal (individual traits) and external (social-economic environment) factors when investigating how female managers’ happiness is impacted. Also, this study challenges the traditional wisdom on the relationship between female managers’ job satisfaction and work-home conflict. This study extends the literature by investigating the impacts of female managers’ masculine behavior on their happiness. This study is useful for promoting female managers' leadership effectiveness and happiness.